2021
DOI: 10.9758/cpn.2021.19.4.786
|View full text |Cite
|
Sign up to set email alerts
|

First Manic Attack During COVID-19 Treatment: A Case Report

Abstract: On March 11, 2020, the World Health Organization declared that the infection of novel coronavirus identified in Wuhan, China, is a pandemic. Various studies have shown that SARS-CoV-2 infection can trigger psychiatric effects such as anxiety, depression, and bipolar disorder. Here, we reported a case with no significant psychiatric history who experienced first-episode mania during the COVID-19 treatment. On the third day of hospitalization, the patient's mood was elevated, she thought she can treat other pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The severity of COVID-19 was different among them, most often it was mild or moderate infection, and the manic symptoms developed at varying time intervals from the onset of COVID-19 symptoms. In three patients, SARS-CoV-2 infection was not confirmed by a formal test, but only on the basis of the clinical picture and characteristic imaging changes in the lungs [ 27 , 31 , 32 ]. The most common symptoms of mania among them were: insomnia, elevated mood, agitation, irritability, delusions, grandiosity and talkativeness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of COVID-19 was different among them, most often it was mild or moderate infection, and the manic symptoms developed at varying time intervals from the onset of COVID-19 symptoms. In three patients, SARS-CoV-2 infection was not confirmed by a formal test, but only on the basis of the clinical picture and characteristic imaging changes in the lungs [ 27 , 31 , 32 ]. The most common symptoms of mania among them were: insomnia, elevated mood, agitation, irritability, delusions, grandiosity and talkativeness.…”
Section: Resultsmentioning
confidence: 99%
“…The most common symptoms of mania among them were: insomnia, elevated mood, agitation, irritability, delusions, grandiosity and talkativeness. Acute manic episode was diagnosed in 26 patients [ 24 , 25 , 26 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], hypomanic episode in 3 [ 32 ], steroid-induced mania in 4 [ 41 , 42 , 43 , 44 ], delirious mania in 2 [ 45 , 46 ], and a full diagnosis of BD was given in 1 patient [ 47 ]. The details of the patients are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main mania symptoms experienced in the cases analyzed include classical presentations of mania: insomnia ( 22 , 26 ) abnormal behavior ( 23 , 24 , 27 ), delusions ( 30 , 31 ), irritability ( 34 , 36 ), agitation ( 35 ), aggressive behavior ( 33 , 37 ), anxiety ( 37 ), impaired concentration ( 21 ), persecutory beliefs ( 30 ), auditory hallucinations ( 21 , 25 ), grandiose ideas ( 21 , 28 , 29 ). These findings support the hypothesis that the psychiatric condition experienced is no other than a manic episode, therefore not representing a separate diagnostic entity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the hypothesis that the pandemic social consequences themselves can be triggering factors for a previously unknown BD [as happened in some case reports analyzed: Uzun et al ( 36 ), Varsak et al ( 37 ), Meltem et al ( 32 )] or an exacerbating factor for those who had already been diagnosed with BD ( 52 , 53 ), this appears to be relevant, as previous studies have already shown that social disasters can exacerbate BD mania symptoms but no other psychiatric disorders ( 54 ). Lockdown measures adopted to embank the pandemic influenced some of those factors which are crucial in mood maintenance in BD, such as sleep and social interactions, therefore possibly causing exacerbation of the mood disorder ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although few, cases of mania and psychosis associated with COVID‐19 infection have been reported in the literature. 3 , 4 In this case, we present a female patient who experienced their first manic episode during the course of a COVID‐19 infection, with which she was infected after an incidental IVF treatment.…”
Section: Introductionmentioning
confidence: 99%